Rights and representation support justice across aquatic food systems - Hicks, Christina; Gephart, Jessica; Koehn, Zachary; Takeshima, Shin‑nosuke; Payne, Hanna; Allison, Edward H.; Belhabib, Dyhia; Cao, Ling; Cohen, Philippa; Fanzo, Jessica; Fluet-Chouinard, Etienne; Gelcich, Stefan; et al. (Nature Research, 2022)
Injustices are prevalent in food systems, where the accumulation of vast wealth is possible for a few, yet one in ten people remain hungry. Here, for 194 countries we combine aquatic food production, distribution and consumption data with corresponding national policy documents and, drawing on theories of social justice, explore whether barriers to participation explain unequal distributions of benefits. Using Bayesian models, we find economic and political barriers are associated with lower wealth-based benefits; countries produce and consume less when wealth, formal education and voice and accountability are lacking. In contrast, social barriers are associated with lower welfare-based benefits; aquatic foods are less affordable where gender inequality is greater. Our analyses of policy documents reveal a frequent failure to address political and gender-based barriers. However, policies linked to more just food system outcomes centre principles of human rights, specify inclusive decision-making processes and identify and challenge drivers of injustice.